التوازن الحراري بين جسم الإنسان والوسط المحيط - حسن, أيوب عيسى (Latakia University Journal -Engineering Sciences Series, 2019)
منذ بداية ظهور الإنسان على كوكب الأرض كان من صلب اهتماماته الحفاظ على جسمه، ووقايته من تأثير الوسط المحيط، وضمان توازنه الحراري المتمثل في التبادل الحراري بين جسمه والوسط المحيط، والذي تختلف قيمته باختلاف فصول السنة. يتركّز اهتمام الكثير من الباحثين في الوقت الراهن وبمختلف اختصاصاتهم، على تأمين الشروط المريحة لحياة الإنسان. سندرس في هذا البحث التبادل الحراري بين جسم الإنسان والوسط المحيط بغية معرفة احتياجاته المولِّدة للطاقة، كالطعام والشراب والتنفس، وذلك لضمان استمرار حياته الطبيعية وتمتعه بقدرته الكاملة، وبأفضل حالات نشاطه. يعتمد ذلك على تحليل التبادل الحراري بين جسم الإنسان والوسط المحيط، والطرق التي يتم فيها هذا التبادل ووضع البرنامج الحاسوبي الملائم. Since their first days on Earth, the greatest interest of humans has been to take care of their bodies and protect them from the effects of surroundings as well as maintaining the heating balance represented in the heat transfer between their bodies and surroundings, with seasonal variance. The interests of many researchers, with their various specializations, currently focus on providing people with good living conditions. In this paper we will study the balance between the human body and the surroundings to know a human's energy-producing needs, such as food, water and breathing, needed for the continuation of his normal life, securing an energetic and fully active life. That depends on the analysis of heat transfer between the human body and the surroundings, knowing the heat transfer methods, and using a suitable computer program.